Enantioselective Borylation of Aromatic C-H Bonds with Chiral Dinitrogen Ligands - Su, Bo (Angew Chem Int Ed Engl, 2017)
The borylation of C-H bonds catalyzed by transition metals has been investigated extensively in the past two decades, but no iridium-catalyzed enantioselective borylation of C-H bonds has been reported. We report a set of transition metal-catalyzed enantioselective borylations of aromatic C-H bonds. This reaction relies on a set of newly developed iridium catalysts ligated by chiral quinolinyl oxazoline ligands. This process proceeds under mild conditions with good to excellent enantioselectivity, and the borylated products can be converted to enantioenriched derivatives containing new C-O, C-C, C-Cl, or C-Br bonds.